Analisis Kesejahteraan Psikologis, Konsep Diri dan Hubungannya dengan Kinerja Guru PJOK Sekolah Menengah Atas Se-Kota Langsa - Navera, Prista Cindi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to analyze the relationship between psychological well-being and self-concept on the performance of high school PJOK teachers in Langsa City. The research method used in this research is a quantitative approach with a correlational descriptive method. The sample in this research was 21 PJOK high school teachers in Langsa City. Data was collected using observation, questionnaires and documentation. Quantitative data analysis consisted of normality test, linearity test, homogeneity test, and hypothesis test using SPSS version 26 software. Based on the results of data analysis, it showed that there was a significant relationship between psychological well-being and self-concept and performance with a significance of 0.03 where (p< 0.05) and has a correlation coefficient of 0.384. Where the psychological well-being value is higher (39.6%) compared to the self-concept value (27.9%). Conclusion, that there is a significant positive relationship between job satisfaction and psychological well-being Keywords: Psychological Well-being, Self-Concept, Performance